2017
DOI: 10.1590/0103-6440201701610
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Retrospective Study of Avulsion Cases in a Public Brazilian Dental Trauma Service.

Abstract: This study assessed the epidemiological characteristics and management of the permanent teeth avulsion cases attended in a Brazilian dental trauma service from December 2005 to August 2016. A retrospective study was conducted of case records of 93 patients involving 139 avulsed teeth. Data included sex, age, trauma etiology, location of the accident, number and position of avulsed teeth, and presence and type of associated traumatic lesions. Management of the avulsed teeth was addressed as: time elapsed until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 24 publications
1
36
0
5
Order By: Relevance
“…The male: female ratio of 1.5:1 in both periods 1 and 2 was similar to other studies. [13][14][15] Other than that, the transmission control measures during the epidemic had an influence on the epidemiology of TDIs, which included the number of patients, age, time since injury to the clinic visit, etiology, tooth location, and the type of injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The male: female ratio of 1.5:1 in both periods 1 and 2 was similar to other studies. [13][14][15] Other than that, the transmission control measures during the epidemic had an influence on the epidemiology of TDIs, which included the number of patients, age, time since injury to the clinic visit, etiology, tooth location, and the type of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified into five agegroups (0-6, 7-12, [13][14][15][16][17][18], and ≥60 years old). The time since injury to the clinic visit was classified into four groups (0-1 hour, 2-6 hours, 7-24 hours, 2-7 days, and >7 days).…”
Section: Materials and Me Thodsmentioning
confidence: 99%
“…The 10 m/s velocity of impact was based on previous studies in which bicycle accidents were shown to be common causes for dental trauma . The 10 m/s impact velocity simulates a patient involved in a bicycle collision, accident or fall …”
Section: Discussionmentioning
confidence: 99%
“…26,27 The 10 m/s velocity of impact was based on previous studies in which bicycle accidents were shown to be common causes for dental trauma. 28,29 The 10 m/s impact velocity simulates a patient involved in a bicycle collision, accident or fall. 30 In this study, a 100N functional biting load was simulated for comparison with the 10 m/s impact model.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate replantation of an avulsed permanent tooth is the treatment of choice and the prognosis of the avulsed tooth depends on timely intervention and storage media ( 9 , 10 ). Most of the time, parents are the first to encounter the child at the time of injury ( 11 ), so their knowledge about quick intervention and storage media is of utmost essential to decide the outcome of avulsed tooth ( 12 ).…”
Section: Introductionmentioning
confidence: 99%